A methodology of risk assessment, management, and coping actions for nuclear power plant (NPP) hit by high-explosive warheads. (October 2020) - Ornai, David; Elkabets, Sima Michal; Kivity, Yosef; Ben-Dor, Gabi; Chadad, Liran; Gal, Erez; Tavron, Barak; Gilad, Erez; Levy, Robert; Shohet, Igal M.
Highlights: A detailed LOCA scenario analysis in an AP1000 NPP was carried out. Combined effect of bomb fragmentation and blast loading model was developed. Cylindrical fragmentation and the Kingery-Bulmash blast model were implemented. Comprehensive risk assessment methodology was developed. Seismic fragility curves were adjusted using airplane crash acceleration limits. Abstract: A detailed Loss of Coolant Accident (LOCA) analysis in an AP1000 NPP was performed, followed by a definition of the vulnerability analysis principles, and analysis of blast loads and fragments impact created by a nearby explosion. The AP1000 NPP performs excellently to small-break LOCA due to in-structure shock, with the 10 CFR 50.46 Acceptance Criteria fully accomplished. Impulsive dynamic loads resulting from blast waves and fragments impact of GBU-28 (Guided Bomb Unit) were considered for a nearby explosion. We model the structure and the main reactor components using the MSC/Dytran code to obtain accurate internal acceleration levels at critical points. We account for the appropriate blast wave interaction with the soil and the soil interaction with the containment structure, rather than using empirical formulas. The model includes the shielding structure with its concrete base, the support structures for the reactor, the steam generators, and the pressurizer. The combined effect of bomb fragmentation and blast loading was also considered using a cylindrical fragmentation model and the blast model of Kingery-Bulmash, assuming a hemispherical charge. A comprehensive risk assessment methodology composed of four phases was developed. The methodology is comprised of: (I) System analysis, (II) Hazard analysis, (III) Damage assessment, and (IV) Risk analysis of the in-structure shock consequences. Using seismic fragility curves for analysis of the expected failure modes according to explosion events faced difficulties since no published data was found. Adjustments to these fragility curves were made using median acceleration limits on components designed to withstand airplane crash, together with standard deviations taken from the given earthquake fragility tables. The findings reveal that the probabilities of failure of the reactor coolant system components resulting from a GBU-28 nearby hit, namely the pressurizer, the cooling pumps, and valves are quite high (greater than 1∙10 −4 ).